Optimalisasi Pengelolaan Laboratorium IPA Dalam Upaya Peningkatan Motivasi Belajar Peserta Didik: Studi Kasus Di SMA Negeri 3 Kota Tasikmalaya - Odang Sobarman (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
This research was motivated by the motivation of students at SMAN 3 Tasikmalaya was not optimal. this is related to optimizing the management of science laboratories. The objectives of this study are: 1) Optimization of science laboratory management in an effort to increase student learning motivation; 2) obstacles faced in optimizing the management of science laboratories in an effort to increase student learning motivation; 3) Obstacle management solutions to optimize the management of science laboratory facilities in an effort to increase student learning motivation. Research data was obtained from informants, namely principals, laboratory heads, science teachers and students. The data collection tools used in this study are interviews, observations, documentation studies, and carrying out triangulation, then the data is processed by data reduction, data presentation, drawing conclusions and verifying data. The results of this study show that the optimization of science laboratory management in an effort to increase student motivation at SMAN 3 Tasikmalaya in terms of planning aspects; organizing; implementation (actuating); and controlling, has been well optimized. However, there is an aspect that needs to be improved, namely the need for an evaluation to be carried out related to the management of the science laboratory, because there are still students who have not shown an increase in their learning motivation